Challenges of CPS/IoT Network Architecture in 6G Era - Takahiko Kato; Norihiro Fukumoto; Chikara Sasaki; Atsushi Tagami; Akihiro Nakao (IEEE Access, 2024)
Cyber Physical System (CPS) and Internet of Things (IoT) have attracted attention as a promising technology for the future society. Although the 6th generation mobile system is expected to work as the CPS/IoT platform, the specific technical requirements are not studied thoroughly. In this paper, we take application driven approach focusing on three applications, eHealth, smart manufacturing, and smart city, to identify mandatory technical requirements for the 6G mobile core network architecture to realize CPS/IoT systems. Specifically, this paper gives the following three contributions. First, we investigate several use cases in the applications listed above and list up the requirements for the core network, i.e., the massive connectivity, the flexible SLA, the ambient IoT device accommodation, the wireless sensing function, and the AI-aware data sharing. Second, we identify the issues to satisfy those requirements in the current 5G technologies. Lastly, we pick up the 6G architectures proposed currently and discuss their pros and cons based on the requirements and issues pointed out.